Interfacial engineering of Ru–S–Sb/antimonene electrocatalysts for highly efficient electrolytic hydrogen generation in neutral electrolyte. Issue 73 (22nd August 2019) - Li, Yan; Chen, Junxiang; Huang, Junheng; Hou, Yang; Lei, Lecheng; Lin, Wanzhen; Lian, Yaping; Zhonghua, Xiang; Yang, Huang-Hao; Wen, Zhenhai
Abstract : The enhancement of Ru–H bonding strength caused by the formation of Ru–S–Sb bond majorly contributes to the significantly improved HER activity. Abstract : The development of high-kinetic catalysts for the hydrogen evolution reaction (HER) in a neutral electrolyte is of great importance but unfortunately remains a challenge so far. Herein, we report hybrids with abundant Ru–S–Sb bonds and engineered ultrathin antimonene (Ru–S–Sb/antimonene) as highly kinetic, active, stable electrocatalysts for the HER in an aqueous neutral electrolyte. Experiments and density functional theory (DFT) calculations reveal that Ru–S–Sb bonds coupling with antimonene synergistically work to promote HER activity. The present study brings us one step closer to understand the structure–composition–property relationships and practical electrolytic H2 production.